Resonances in electron-capture total cross sections for C4+ and B5+ collisions with H(1s) - Barragán, P.; Errea, L. F.; Guzmán, F.; Méndez, L.; Rabadán, I.; Ben-Itzhak, I. (My University, 2010)
Quantal calculations of electron-capture and elastic cross sections have been carried out for collisions of C4+ and B5+ with H(1s) at collision energies 0.00025<E<0.02 eV, where the cross sections show numerous resonances. Positions and widths of the resonances are studied by using the phase-amplitude method.